Effects of a congested match schedule on isometric muscle strength performance in elite futsal players - Gantois, P.; Farinha, A.; Fonseca, F. d. S.; Ribeiro, J. (The Journal of Strength and Conditioning Research, 2026)
This study investigated the effects of a congested tournament schedule on isometric muscle strength performance in elite futsal players. Twelve elite-level outfield male futsal players (mean ± SD: age = 27.42 ± 5.60 years, body mass = 76.74 ± 8.91 kg, and height = 1.75 ± 0.04 m) from a top-tier Portuguese league team participated in this study. Postmatch neuromuscular fatigue was assessed by measuring the isometric strength of the hip adductors, abductors, and knee flexors on both dominant and nondominant sides. Baseline measurements (MD1) were taken before the first match, with follow-up tests conducted at 24 hours (MD2), 48 hours (rest day), and 72 hours (MD3) postbaseline. Adductor muscle strength in the dominant limb reduced significantly at MD2 (p = 0.026; effect size [ES] = 0.20) and rest day (p = 0.045; ES = 0.28) compared with MD1. Dominant-side hip abduction strength was significantly lower at MD2 (p = 0.003; ES = 0.62), on the rest day (p < 0.005; ES = 0.56), and at MD3 (p = 0.045; ES = 0.41) relative to baseline. No significant changes were found in knee flexor strength across time points (p > 0.05). In conclusion, these findings indicate that a congested schedule reduced hip adduction and abduction strength among elite futsal players, with prolonged decreases in hip abduction strength. By contrast, hip adduction strength displayed faster recovery after a rest day.